Identifying Thermal Dynamics for Precision Motion Control. Issue 15 (2019) - Evers, Enzo; Tuijl, Niels van; Lamers, Ronald; Oomen, Tom
Abstract: Thermal-induced deformations are becoming increasingly important for the control performance of precision motion systems. The aim of this paper is to identify the underlying thermal dynamics in view of precision motion control. Identifying thermal systems is challenging due to large transients, large time scales, excitation signal limitations, large environmental disturbances, and non-linear behavior. An approach for non-parametric identification is developed that is particularly suitable for thermal and mechanical aspects in mechatronic systems. In particular, prior knowledge of several domains can be directly specified. Additionally, the non-parametric model is used as a basis for parameter estimation of a grey-box model. The presented methods form a complete framework that facilitates the implementation of advanced control techniques and error compensation strategies by providing high-fidelity models, enabling increased accuracy and throughput in high precision motion control.